Managers' Perceptions On Best Business Practices In Low Cost Carriers Industry In Indonesia - Fernando, Yudi (2011)
The objective of the study was to develop a low-cost carriers’ excellent business model, with the emphasis on the internal and external organizational competence. The triangulation methods were proposed to contribute to the body of knowledge and give a new insight for business practices. The research process started on the preliminary data gathering. To get a new insight on the theoretical model development, the present study provides benchmarking results on the two best low-cost carrier practices in the six regions. Further, international phone call interviews were conducted to explore the managers’ perceptions and interpretations of the internal service quality. Indonesia has been chosen fit for the assessment of the model because it was listed as one of the countries that have more than five aircraft crashes in the last few years. A survey was conducted and the data obtained from 209 sets of usable questionnaires. In quantitative study, unit analysis is strategic business unit and resource based view serves as underlying theory. Based on quantitative findings, it is found that a positive relationship exists between internal marketing and internal service quality. The current study also finds that internal marketing and internal service quality are significantly related with airline business performance. The synergy between low-cost carrier and the supplier produces excellent service and strengthen airline business performance. The study is drawn to the conclusion that both qualitative and quantitative findings are complementing each other.